Structural and Functional Hippocampal Changes in Subjective Cognitive Decline From the Community - Liang, Lingyan; Zhao, Lihua; Wei, Yichen; Mai, Wei; Duan, Gaoxiong; Su, Jiahui; Nong, Xiucheng; Yu, Bihan; Li, Chong; Mo, Xiaping; Wilson, Georgia; Deng, Demao; et al. (Frontiers in Aging Neuroscience, 2020)
Background: Recently, subjective cognitive decline(SCD) has been described as the earliest at-risk state of Alzheimer's disease(AD), and drawn attention of investigators. Studies suggested that SCD-community individuals may be at an earlier state of SCD than SCD-clinic patients, therefore, to investigate the early changes of the brain may provide guidance for intervention and treatment of the disease. We sought to investigate the changes of structure and functional connectivity of the hippocampus in individuals with SCD recruited from the community using structural and resitng-state functional MRI(fMRI). Methods: Thirty-five SCD patients and 32 healthy controls were recruited. Resting-state fMRI data and high-resolution T1-weighted images were collected. Whole-brain voxel-based morphometry was used to examine the brain structural changes. We also used the hippocampal tail and the whole hippocampus as seeds to investigate functional connectivity in SCD. Results: Individuals with SCD showed significant gray matter volume decreases in the bilateral hippocampal tails and enlargement of the bilateral paracentral lobules. We also found that individuals with SCD showed decreased hippocampal tail resting-state functional connectivity(rsFC) with the right medial prefrontal cortex (mPFC) and the left Hippocampal Changes in SCD temporoparietal junction (TPJ) and decreased whole hippocampus rsFC with the bilateral mPFC and TPJ. These results showed significantly correlation with Montreal Cognitive Assessment (MoCA) scores. Conclusion: SCD is associated with structural and functional changes of the hippocampus, and these changes may serve as potential biomarkers of SCD.The Declaration of Helsinki, and the study was registered in http://www.chictr.org.cn.The Clinical Trial Registration Number was ChiCTR-JPR-16009144.